2019
DOI: 10.1002/acn3.730
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐PrPC antibody rescues cognition and synapses in transgenic alzheimer mice

Abstract: Objective Amyloid‐beta oligomers (Aßo) trigger the development of Alzheimer's disease (AD) pathophysiology. Cellular prion protein (PrPC) initiates synaptic damage as a high affinity receptor for Aßo. Here, we evaluated the preclinical therapeutic efficacy of a fully human monoclonal antibody against PrPC. This AZ59 antibody selectively targets the Aβo binding site in the amino‐terminal unstructured domain of PrPC to avoid any potential risk of direct toxicity. Methods Potency of AZ59 was evaluated by binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…One year later, Chen and co-workers showed that both N -terminal residues 23–27 and 92–110 were critically important for binding [ 36 ]. The importance of these two sequence regions was then confirmed by later reports [ 13 , 14 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…One year later, Chen and co-workers showed that both N -terminal residues 23–27 and 92–110 were critically important for binding [ 36 ]. The importance of these two sequence regions was then confirmed by later reports [ 13 , 14 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionsupporting
confidence: 55%
“…Previous studies have suggested that the cell surface protein PrP C mediates the toxicity of Aβ 42 oligomers by binding to them and affecting synaptic plasticity and other neuronal functions [ 13 , 14 , 15 , 16 , 17 , 18 ], although a general consensus on this point has not yet been found [ 19 , 20 , 21 ]. One PrP C region of the sequence thought to be involved in Aβ 42 binding encompasses approximately residues 95–110 [ 13 , 14 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 ]. An antibody raised against residues 93–109 of PrP C (anti-PrP C 93–109 GD11) and a synthetic peptide corresponding to residues 98–107 (PrP 98–107 ) were found to inhibit the toxicity of the Aβ 42 ADDLs to organotypic hippocampal slices, whereas a control PrP 213–230 peptide did not have any such effects [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with an antibody against residues 93–109 of PrP C , 6D11, can prevent neuronal cell death by oligomeric Aβ42 and rescues cognitive deficits in APP/PS1 transgenic mice, while another antibody against residues 144–152 of PrP C , 6H4, fails to block oligomeric Aβ-induced neuronal toxicity (Chung et al, 2010; Kudo et al, 2012). Recently, another antibody against resides 23–111 of PrP C was reported to rescue synapses and cognitive deficits in APP/PS1 mice (Cox et al, 2019).…”
Section: Prpc Mediates Neurotoxicity By Aβ Oligomersmentioning
confidence: 99%
“…This regimen of intact anti-PrPc antibody treatment normalized both the behavioral disturbances and synaptic losses of AD mice relative to control mice for up to 1 month after the last dose. 28 This dramatic outcome requires validation in other types of AD mice with Fab as well as intact antibody, and with additional anti-PrPc antibody controls.…”
Section: Initiating Eventsmentioning
confidence: 99%
“…Such therapy will reduce and delay the synaptic dysfunction and cerebral microvascular diseases attributable to binding of these neuropathogenic proteins to their neuronal and endothelial receptors, as already suggested by a few early studies in animal models. 28,44 It is expected that therapies directed to the later amplification processes may include complement C3 convertase inhibitors, neuronal survival factors such as leukemia inhibitory factor (LIF) and SOD mimetics. Although these agents may be beneficial even late in the course of AD, their effects are unlikely to be as striking as those of antibodies and drugs preventing initial actions of primary neuropathic proteins on neurons.…”
Section: Therapeutic Approachesmentioning
confidence: 99%